VISUAL KINESTHETIC BASED INSTRUCTIONAL STRATEGIES IN ISLAMIC RELIGIOUS EDUCATION TO ENHANCE WORSHIP COMPREHENSION AMONG DEAF LEARNERS - Maharani, Ria; Kustati, Martin; Sepriyanti, Nana; Rahman, Arsanur (As-Sulthan Journal of Education, 2026)
Islamic Religious Education for deaf students requires adaptive instructional strategies because auditory limitations make it difficult for them to fully understand religious material when it is delivered verbally. This study aims to develop and analyze a visual kinesthetic based learning strategy to enhance students’ understanding of basic Islamic worship practices, particularly wudu and prayer. Using a qualitative approach with a case study design, data were collected through observations, in depth interviews, and documentation, then analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings show that the use of visual media (sequential images, demonstrative videos, and worship sign cards) combined with kinesthetic activities (prayer movement exercises, wudu simulations, and repeated demonstrations) significantly improves student engagement and strengthens procedural memory among deaf learners. This strategy also fosters greater confidence and independence in performing worship because learning is presented in a more concrete, structured, and meaningful manner. Therefore, visual kinesthetic based Islamic Religious Education instruction is proven to be an effective, inclusive, and responsive pedagogical approach that aligns with the unique learning needs of deaf students and offers practical recommendations for teachers in designing inclusive religious education.